Geochemical association of Pu and Am in selected host-phases of contaminated soils from the UK and their susceptibility to chemical and microbiological leaching. (April 2015) - Kimber, Richard L.; Corkhill, Claire L.; Amos, Sean; Livens, Francis R.; Lloyd, Jonathan R.
Abstract: Understanding the biogeochemical behaviour and potential mobility of actinides in soils and groundwater is vital for developing remediation and management strategies for radionuclide-contaminated land. Pu is known to have a high Kd in soils and sediments, however remobilization of low concentrations of Pu remains a concern. Here, some of the physicochemical properties of Pu and the co-contaminant, Am, are investigated in contaminated soils from Aldermaston, Berkshire, UK, and the Esk Estuary, Cumbria, UK, to determine their potential mobility. Sequential extraction techniques were used to examine the host-phases of the actinides in these soils and their susceptibility to microbiological leaching was investigated using acidophilic sulphur-oxidising bacteria. Sequential extractions found the majority of 239, 240 Pu associated with the highly refractory residual phase in both the Aldermaston (63.8–85.5 %) and Esk Estuary (91.9–94.5%) soils. The 241 Am was distributed across multiple phases including the reducible oxide (26.1–40.0%), organic (45.6–63.6%) and residual fractions (1.9–11.1%). Plutonium proved largely resistant to leaching from microbially-produced sulphuric acid, with a maximum 0.18% leached into solution, although up to 12.5% of the 241 Am was leached under the same conditions. If Pu was present as distinct oxide particles in the soil, then 241 Am, a decay product of Pu, would be expected to be physically retained in the particle. The differences in geochemical association and bioleachability of the two actinides suggest that this is not the case and hence, that significant Pu is not present as distinct particles. These data suggest the majority of Pu in the contaminated soils studied is highly recalcitrant to geochemical changes and is likely to remain immobile over significant time periods, even when challenged with aggressive "bioleaching" bacteria. Highlights: Pu in the contaminated soils is associated with the recalcitrant residual phase. Differences observed between Am and Pu geochemical behaviour. Pu remobilization is very limited but migration may occur over longer time frame.